Moderating role of risk management effectiveness on corporate social responsibility- corporate performance relationship - Husaini Husaini; Ridwan Nurazi; Saiful Saiful (Cogent Business & Management, 2023)
This study is designed to provide empirical evidences on the conditional influence corporate social responsibility (CSR) on corporate accounting and market performance. This study considers risk management (RM) as a conditional or moderating variable. Accounting performance was proxied by return on assets (ROA), earnings per share (EPS), and net profit margin (NPM), while market performance was proxied by Tobin-Q and stock price. Furthermore, those proxies form corporate performance variable based on factor analysis. CSR measured using the Global Reporting Initiative (GRI G4) Index. Meanwhile, RM was measured using total risk management proxy. By applying purposive sampling method, 253 non-financial companies were selected as a sample of this study. The Structural Equation Modeling (SEM) with the WarpPLS approach was used for data analysis. This study found that the corporate social responsibility has a positive effect on corporate performance, and the relationship between corporate social responsibility and corporate performance will be stronger if corporate risk management is applied optimally. The findings of this study imply that the good corporate performance will be achieved since a company discloses more CSR information and runs effective risk management as well.
Keywords: M21; M14; M40; 650; Corporate social responsibility; corporate performance; risk management; corporate governance